Aspects Of Physical Fitness Of Eye And Hand Coordination In SMPN 1 Bangkalan Students - Ismiatin Ismiatin; Fajar Hidayatullah; Khoirul Anwar (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
This study was conducted to determine the aspects of physical fitness in SMPN 1 Bangkalan students using quantitative descriptive research with survey and measurement methods. The population of this study were students of Bangkalan 1 State Junior High School who were in class VII and took the best 30 students. The results of the research that has been carried out on this Validity test get valid results because the value is more than 0.970> 0.361, the reliability test is said to be reliable because it has Cronbach's alpha value> significant at 0.974> 0.05 then this reliability result is declared reliable. While in the test the significance value of 0.038 > 0.05, it can be concluded that the residual value is normally distributed.